Establishing reference sizes for the rear portion of the foot for use in designing lasts for women's shoes. (2nd January 2017) - Nakayama, Kentaro; Abe, Kaoru; Nagai, Keiko; Oi, Kazuko; Oi, Hiroshi
Abstract : The current Japanese Industrial Standards (JIS) for shoes (S 5037) specify foot length, ball girth, and ball width, providing a reference for shoe last manufacture and shoe selection. However, the JIS as well as International Organization for Standardization standards and national standards in other countries for shoes are based only on measurements of the forefoot; no reference sizes have been established for the rear portion of the foot. This is thought to be one cause of problems such as shoe sores on the heel region and shoes slipping off the heels. Few studies and reports have investigated the rear portion of the foot, with research into the shape of the heel (heel curve) being particularly scarce. This study used a purpose-built device to measure the height of the maximum projection of the heel curve in 12 pairs of shoes of the same size and a three-dimensional foot scanner to measure the foot length, ball girth foot, dorsal height, and height of the maximum projection of the heel of the foot in 473 healthy female subjects (946 feet) aged at least 12 years old. There was no uniformity in the heights of the maximum projection of the heel curves. However, a correlation was observed between the height of the maximum projection of the heel and foot length and ball girth. The present findings were used to determine reference sizes for the rear portion of women's feet in conjunction with the JIS.